ANALYSIS OF DRAINAGE CHANNEL CAPACITY IN CIREMAI RAYA, LARANGAN SUB-DISTRICT OF CIREBON CITY - Akbar Winasis; Ohan Farhan; Heri Mulyono (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2021)
The perumnas gunung area is one of the areas in the Larangan sub-district, Harjamukti Subdistrict, Cirebon City, whose drainage system greatly disturbs the activities of the population in Cirebon City because when heavy rain causes the high volume of water in the drainage so that it comes out to the highway and is very disturbing it can also cause congestion.To solve the problem of inundation and flooding, it requires maximum rainfall data, population density data and hydraulic data from direct observation at the research location. From the rainfall data, the intensity of the rainfall is calculated, then the standard deviation is calculated to get the return period value using the Gumble formula. From the calculation of the Return Period, the calculation of the flood discharge is carried out using a rational method and calculating the discharge of the existing channel. Calculation of the capacity of the existing channel discharge is carried out by calculating the discharge of rainwater and discharge of household wastewater.From the calculation of Hydrology and Hydraulics, the value of Rainfall Intensity is 46.632 mm / day, the overall channel discharge = 0.603 m3 / s, the calculation of the total discharge from household wastewater and rainwater discharge for the 2-year return period is 0.0076 m3 / s. . From the calculation results, the authors conclude that the dimensions of the existing canal can still accommodate the flow of rainwater and household wastewater. The solution to overcome flood inundation on Jalan Ciremai Raya, it is necessary to normalize the drainage channel so that the drainage channel can function properly.